STRATEGI PROMOSI DALAM MENINGKATKAN PENERIMAAN PESERTA DIDIK BARU DI MADRASAH TSANAWIYAH NEGERI 5 KENALI BESAR KOTA JAMBI - Salmiyah; Raudhatul Jannah, Siti; Pirdaus, Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze promotion strategies in increasing new student enrollment at Madrasah Tsanawiyah Negeri 5 Kenali Besar, Jambi City. The background of this research is the increasing competition among educational institutions, which requires madrasahs to implement effective and sustainable promotional strategies in order to attract public interest and strengthen institutional trust. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, administrative staff, and the admission committee. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the promotion strategies were implemented through the use of digital media and printed media by presenting student activities, extracurricular programs, academic and non-academic achievements, and detailed enrollment information. These strategies were proven to be effective in increasing public trust and attracting prospective students. Supporting factors included the school’s A accreditation status, strong collaboration among the admission committee, teachers, and educational staff, students’ achievements, and limited competition from similar schools in the surrounding area. Meanwhile, the inhibiting factors were the community’s limited understanding of the online admission system and the low participation of nearby schools in disseminating information. The solutions implemented included providing registration assistance for prospective students and parents, as well as redistributing brochures to surrounding schools to expand the dissemination of information and facilitate the enrollment process